PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM TIRTA MANGUTAMA BADUNG - Dwijayanti, Made Nensy; Dewi, A.A Sagung Kartika (E-Jurnal Manajemen, 2015)
The purpose of this study is to determine the effect of compensation and work environment on employee job satisfaction at PDAM Tirta Mangutama Badung.This study was conducted In PDAM Tirta Mangutama Badung with a sample of 66 respondents and the data were analyzed by linear regression analysis techniques berganda.Hasil analysis in this study found that the compensation and work environment partially positive and significant impact on job satisfaction. The most dominant variable affecting job satisfaction is the work environment. The variable compensation indicator is the lowest value allowance, therefore, companies must pay attention to the nominal increase in allowances in line with the increase in corporate profits. In the work environment variables lowest value indicator is lighting, the company must adjust the lamp power used by the magnitude of the room so that employees feel comfortable while working. If it can be considered properly then it can have a positive impact and improve employee satisfaction at PDAM Tirta Mangutama Badung.
Keywords: Kepuasan Kerja; Kompensasi; Lingkungan Kerja